Interaction Process and Chinese EFL Learners' Proficiency Development A Cognitive and Interactionist Approach - Gu, Shanshan (Springer Singapore, 2018)
This book provides readers a better understanding of the interaction-learning relationship in the English as a Foreign Language (EFL) context. It introduces theories on input, output, and learners' internal mechanisms, and presents the pedagogical implications of how to adapt focus-on-form instruction in Chinese EFL classrooms. As such, it will be of particular interest to those readers who want to explore the relationship between interaction and language acquisition.